2008 10th IEEE International Workshop on Advanced Motion Control 2008
DOI: 10.1109/amc.2008.4516045
|View full text |Cite
|
Sign up to set email alerts
|

A linear programming approach to design robust input shaping

Abstract: Input shaping is an established technique to generate inputs that move flexible mechanical systems with little or no residual vibration. While traditional input shaping design strategies are often analytical, the present paper introduces a design method based on numerical optimization. It is shown that, through a careful selection of the optimization variables, objective function and constraints, it is possible to obtain a linear optimization problem. As a result, it is guaranteed that the globally optimal inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Hence, the optimization will restart the factorization of the KKT-matrix. However, this problem is hotstarted by starting the solution from a static controller, which has properties similar to the desired controller [14].…”
Section: Transition Over Timementioning
confidence: 99%
“…Hence, the optimization will restart the factorization of the KKT-matrix. However, this problem is hotstarted by starting the solution from a static controller, which has properties similar to the desired controller [14].…”
Section: Transition Over Timementioning
confidence: 99%
“…to make it more robust [2], to make it faster by allowing negative impulses [5], or including a priori information about the desired trajectory [3]. It has been shown that the input shaping problem can be reformulated in a more general linear programming framework [8], [9]. This generalization considers the system and prefilter as one system of which the total impulse response has to be shaped; i.e., the input shaping prefilter design considers:…”
Section: A Input Shapingmentioning
confidence: 99%
“…a reference step of 1cm. The considered prefilter is designed following the procedure of [8]. In this procedure, negative impulses are allowed as in the predictive prefilter, and such that no saturation takes place for a reference step of 1cm.…”
Section: B Single Step Benchmarkmentioning
confidence: 99%
See 1 more Smart Citation
“…The profile design is not strictly a feedforward control; in terms of predicting the characteristics of the plant system, however, the profile design is considered to be a kind of the off-line feedforward control. Recent research has produced the filtering methods that propose suppressing the frequency component around the resonant frequency (5)- (7) . Hence, profile design methods that use the final state control have also been proposed (8)-(11) .…”
Section: Introductionmentioning
confidence: 99%